2011
DOI: 10.1186/1471-2458-11-586
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COPD and its association with socioeconomic status in China: Findings from China Chronic Disease Risk Factor Surveillance 2007

Abstract: BackgroundSocioeconomic status is likely an independent risk factor for Chronic Obstructive Pulmonary Disease (COPD), but little research has been done in China to study this association in a nationwide sample.MethodsWe used data from the 2007 China Chronic Disease Risk Factor Surveillance of 49,363 Chinese men and women aged 15-69 years to examine the association between the prevalence of self-reported physician diagnosed COPD and socioeconomic status defined by both educational level and annual household inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 28 publications
(34 reference statements)
6
60
4
Order By: Relevance
“…Previous studies have reported a positive relationship between a lower educational level and the prevalence of COPD,13,25,26 although others have reported contradictory results 27,28. A large study of 49,363 participants in The People’s Republic of China showed relationships among low education, low familial income, and COPD, regardless of residing in a rural or urban area 18. However, familial income was not a risk factor for COPD in our study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Previous studies have reported a positive relationship between a lower educational level and the prevalence of COPD,13,25,26 although others have reported contradictory results 27,28. A large study of 49,363 participants in The People’s Republic of China showed relationships among low education, low familial income, and COPD, regardless of residing in a rural or urban area 18. However, familial income was not a risk factor for COPD in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…A low level of education, employment as a manual laborer, and a history of tuberculosis or bronchiectasis were associated with an increased prevalence of COPD in never-smokers. In previous studies, the parameters of socioeconomic status such as education, occupation, marital status, and familial income were closely related to health condition and affected the onset and prognosis of COPD, particularly in never-smokers 9,12,14,17,18. There is no doubt that smoking is a major risk factor for COPD.…”
Section: Discussionmentioning
confidence: 98%
“…Former smokers had a higher prevalence of COPD (9.0%) compared to current smokers (3.3%) and never smokers (2.3%). [9] In another study conducted in china the results were similar where overall prevalence of COPD in the two areas (Liwang and Yunyan) was 9.4%. The prevalence of COPD in both the whole population and a subpopulation of nonsmoking women in rural Yunyan was significantly higher than in urban Liwang (12.0% vs 7.4%, and 7.2% vs 2.5%, respectively).…”
Section: Discussionsupporting
confidence: 61%
“…Previous epidemiological studies in China identified risk factors for COPD, such as smoking and solid fuel use [5] and socioeconomic status [6]. Yet, as in other countries in which these types of surveys have been conducted, differences in disease incidence and the contributing factors may differ between urban and rural areas [7][9]; although, a common factor appears to be air quality, either within the home or the environment in general.…”
Section: Introductionmentioning
confidence: 99%